Memutus Mata Rantai Stunting: Transformasi Pendampingan Keluarga Oleh Tim Stunting Kecamatan Kunduran Blora - Aris Toening Winarni (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to formulate a transformation model for stunting assistance by the Kunduran District Stunting Team, Blora Regency. The study uses qualitative methods with a phenomenological approach through in-depth interviews. The results of the research show that the implementation of the role of companion for stunting families in Kunduran District still faces several obstacles, such as limited competence of companions, less effective counselling methods, barriers to access to health services for stunting families, and early detection and supplementation of at-risk pregnant women. A transformation of the stunting assistance paradigm is needed from the old top-down approach to a dialogical and collaborative model between the assistant and the family. Transformation is required by increasing companions' competence, interactive counselling, an organized referral system, early detection of at-risk pregnant women, and increasing access to nutritional supplementation. With comprehensive transformation, it is hoped that supporting stunted families will be more effective in accelerating the reduction of stunting in Kunduran District and Blora Regency. Regional government support through policies and funding is urgently needed to optimize the transformation of the role of family companions.